Romania’s Transport System Risk Response Plan Measures during the Pandemic within the context of the European Union - Laurențiu DAVID; Frantz Daniel FISTUNG (Communications of International Proceedings, 2021)
From the very beginning of 2020, the health crisis caused by the COVID – 19 pandemic has greatly impacted, among other industrial and service economic areas, the European Community transport sector. It has been, therefore, of utmost importance for the transport officials at both European Community and national levels to react quickly and effectively, in order to limit the damages caused by this environment risk, as well as to make possible the rendering of essential transport activities. This paper focuses on analyzing the risk response plan measures taken by the European Union (EU), and in particular, by Romania, as part of the concerted effort undertaken for ensuring a high level of resiliency of the transport sector. At the same time, the paper highlights the impact on the Romanian transport system caused by the current pandemic, especially, within the commencing months, as well as the actions taken to reduce their impact on the economy and public life. The analysis presented herein, reveals the rapid and prompt risk response plan of the European Union transport officials as a result of their proper risk assessment and analysis of the pandemic. Romania adopted, more or less, the proper stance allowing for further improvement. Given the existing circumstance, the authors propose a set of short and medium range measures that should be adopted, in order to avoid potential bottlenecks caused by the currently reduced level of transport activity. In their analysis, the authors used the multi-criteria analysis of the official statistical data provided by both the authorities of Romania and the European Union.
Keywords: Transport system; Pandemic; European transport policies; Infrastructure